(untitled) (Journal of the College of Languages (JCL), 2022)
Based on the German language department’s theoretical and practical aspects as well as educational programs, the present study discusses the semantic relations in text sentences and their role in the science of translation. Through clarifying the semantic relationship between the text sentence and the methods used to express a news item, a situation or an occurrence and through the statement of the multiple theoretical semantic structures of the text’s construction and interrelation, a translator can easily translate a text into the target language. It is known that language learners face multiple difficulties in writing and creating an integrated, coherent and intelligible text, and the reason for this is their lack of knowledge of semantic relations. Deutsch In dieser Forschungsarbeit gehen die folgenden theoretischen Ausführungen im Zusammenhang mit bestimmten didaktischen Bemerkungen, die im Laufe des Lehrprozesses aufgetreten sind, der Frage der semantischen Relationen in Satzperspektiven nach. Berücksichtigt wurde dabei überdies das Lehrprogramm in der irakischen Germanistikabteilung. Daher besteht das Hauptpostulat dieser wissenschaftlichen Abhandlung in dem Versuch, dieses sprachliche Phänomen im Übersetzen und dessen vielseitige Varianten darzulegen sowie dessen Anwendbarkeit in den Verhandlungen, im praktischen Leben und im Umgang mit den ausländischen Firmen etc. zu klären.